2021
DOI: 10.1007/s42452-020-04005-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple linear regression analysis (MLR) applied for modeling a new WQI equation for monitoring the water quality of Mirim Lagoon, in the state of Rio Grande do Sul—Brazil

Abstract: Accurate assessment of the type and extent of water pollution is a difficult and complicated task. Therefore, the use of the Water Quality Index (WQI) proves to be a useful tool, as this index has the advantage of resulting in a single number that is easy to communicate and understand. One of the statistical methods that can be used to develop a new WQI equation for a given water body is Multiple Linear Regression (MLR). Therefore, this work aims to develop a new WQI equation for Mirim Lagoon through MLR and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 28 publications
1
24
0
1
Order By: Relevance
“…Recently, Singha et al (2021) applied deep learning for predicting WQI with 3 traditional models and found that the deep learning model is a more robust and accurate tool than the traditional model in the prediction of groundwater quality. Valentini et al (2021) introduced a new WQI equation for Mirim Lagoon and evaluated its suitability based on 154 samples collected over three years at seven sampling points in Mirim Lagoon. For forecasting monthly WQI values at the Lam Tsuen River in Hong Kong, Asadollah et al (2021) proposed a new ensemble machine learning algorithm called extra tree regression (ETR).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Singha et al (2021) applied deep learning for predicting WQI with 3 traditional models and found that the deep learning model is a more robust and accurate tool than the traditional model in the prediction of groundwater quality. Valentini et al (2021) introduced a new WQI equation for Mirim Lagoon and evaluated its suitability based on 154 samples collected over three years at seven sampling points in Mirim Lagoon. For forecasting monthly WQI values at the Lam Tsuen River in Hong Kong, Asadollah et al (2021) proposed a new ensemble machine learning algorithm called extra tree regression (ETR).…”
Section: Introductionmentioning
confidence: 99%
“…The value SI � 0.0009 means that the MPA-ANN has an excellent performance according to the limitations in Section 3.4. Furthermore, the Kolmogorov-Smirnov and Shapiro-Wilk tests agree that the residual data are normally distributed depending on the significant values (p value) being more than 0.05 [72,73]. The study's statistical testing findings show the following: (1) Data preprocessing techniques play an essential role in improving data quality, particularly the SSA method.…”
Section: Application Of the Ann Modelmentioning
confidence: 81%
“…The use of nonparametric tests, such as those used in this study, to assess the assumptions of sample distribution of data is something quite consolidated in the literature and several authors have used these tests in studies related to water quality. Furthermore, the KS and SW normality tests are applied in several studies regarding surface or groundwater quality (e.g., Santos et al, 2020;Batista et al, 2021;Leite et al, 2021;Valentini et al, 2021c;Valentini et al, 2021d;Silveira et al, 2021). Santos et al (2021), for example, applied KS and SW tests for evaluate data sampling distribution of in order to know which correlation coefficient would be more appropriate for application of correlation analysis between these data and Water Quality Index calculated in their study.…”
Section: Resultsmentioning
confidence: 99%